2012
DOI: 10.1111/j.1574-6968.2012.02625.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress response in two representative bacteria exposed to atrazine

Abstract: Bacteria are present extensively in the environment. Investigation of their antioxidant properties will be useful for further study on atrazine stress tolerance of bacteria and the defense mechanism of antioxidant enzymes against atrazine or other triazine herbicides. Superoxide dismutase (SOD), catalase (CAT), glutathione S-transferase (GST) and total antioxidant capacity (T-AOC) from one Gram-negative representative strain Escherichia coli K12 and one Gram-positive representative strain Bacillus subtilis B19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 33 publications
2
18
0
1
Order By: Relevance
“…Atrazine induces SOD, catalase and glutathione transferase enzymatic activity in E. coli and other bacteria, and it may induce oxidative stress by causing a redox potential imbalance in bacterial cells that deregulates bacterial metabolism (Zhang et al . ,b). While it remains unknown how Anabaena Fld expression in bacteria confers tolerance to high concentrations of atrazine, the underlying mechanism may be similar to that proposed above for hydrogen peroxide and paraquat‐induced stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atrazine induces SOD, catalase and glutathione transferase enzymatic activity in E. coli and other bacteria, and it may induce oxidative stress by causing a redox potential imbalance in bacterial cells that deregulates bacterial metabolism (Zhang et al . ,b). While it remains unknown how Anabaena Fld expression in bacteria confers tolerance to high concentrations of atrazine, the underlying mechanism may be similar to that proposed above for hydrogen peroxide and paraquat‐induced stress.…”
Section: Discussionmentioning
confidence: 99%
“…; Zhang et al . ,b). Furthermore, many pesticide residues and other organic contaminants are chaotropic and/or hydrophobic substances that induce chaotropicity‐mediated water stress, and secondarily oxidative stress, in microbial cells (Hallsworth et al .…”
Section: Discussionmentioning
confidence: 99%
“…Increased lipid peroxidation (plasma) 63) reported enhanced lipid peroxidation and activity of antioxidant enzymes in male Wistar rats exposed to atrazine. Oxidative stress induced by atrazine was also detected in two bacterial strains (64) and adult female zebrafish (65). In addition, atrazine was found to induce apoptosis in PC12 cells by altering the expression of p53, caspase-3, and caspase-9 (66) and to cause apoptosis-related neurodegenerative damage in the nerve cells (61).…”
Section: Pesticide Type Cell Type / Cell Line Antioxidant Status and mentioning
confidence: 97%
“…And also, a certain evidences confirmed that NPs can damage cells including oxidative stress elicited by ROS (Winnik & Maysinger, 2013). To explore whether oxidative injury would induced by CdS NPs in the respiratory system, we have assessed the changes of several oxidative damage-related indices, including superoxide dismutase (SOD), catalase (CAT), malondialdehyde (MDA) and ROS (Yu et al, 2011;Zhang et al, 2012) induced by CdS NPs in the pulmonary epithelial cell line A549 and rat lung tissues. Additionally, we compared the effect of different CdS NP lengths and discuss the possible mechanisms of action.…”
Section: Introductionmentioning
confidence: 97%